Mediatized Da’wah: The Portrayal of Islamic Relationship Issues on Indonesian Social Media - Zubaidi, Advan Navis (Jurnal Komunikasi Islam, 2025)
This study explores the emergence of Islamic relationship themes on Indonesian social media platforms, specifically Instagram and TikTok. It primarily draws on the concept of the mediatization of religion. A qualitative content analysis was employed in this research. In this regard, the researcher observed several TikTok and Instagram accounts that feature Islamic relationship content and analysed narrative messages, videos, captions, sound effects, and user reactions in the comment sections of those accounts. The findings of this study show that the Islamic relationship theme has emerged as a new alternative to traditional da’wah topics. This shift is largely due to the theme’s social relevance for social media users. Furthermore, Islamic relationship content serves as a counter-narrative to the trend of casual relationships that are increasingly popular among younger generations. This content also constructs and presents an imagined profile of the ideal romantic partner according to Islamic values.